An Examination of the Implementation and Challenges of the Merdeka Curriculum in Madrasah Aliyah: A Case Study on the Al-Qur'an Hadith Subject - Suarni; Sartin; Muliyani Muliyani (South Sulawesi Education Development (SSED), 2023)
The objectives of this study are: 1) Assessing the implementation of the Independent Curriculum in class X Qur'anic Hadith subjects in MAN 1 for the 2022/2023 school year, and 2) Identifying obstacles educators face in the implementation. The method used is descriptive qualitative research. The study subjects included the Deputy Head of Madrasah for Curriculum, Teachers of Qur'anic Hadith, and Students at MAN 1 Kendari. Data collection techniques include observation, interviews, and documentation, with data analysis techniques through data reduction, data presentation, and conclusions. The results showed that implementing the Independent Curriculum in MAN 1 Kendari had been carried out but was not fully successful. In this context, the Merdeka Curriculum is no longer focused on cross-interest; Grade 10 students learn all the basic material, which becomes the basis for determining majors in grade 11. This process includes learning planning in the form of Learning Objectives Flow Planning, Learning Objectives, and Making modules, implementing the learning process through the stages of observing, questioning, collecting information, and strengthening material, as well as assessment, which includes formative and summative functions. These assessments are carried out directly by educators, including cognitive assessments such as knowledge, skills in reading the Qur'an and Hadith, as well as skills in revealing knowledge material, and also through written assessments.